Інформаційні технології як складник інформаційних технологій навчання в історичному контексті - Громов, Євген Володимирович; Ящун, Тетяна Вікторівна (НТУ "ХПІ", 2011)
The concept of information technology of education of a modern context is considered in the article. The historical role of information technology in formation of information technology of education reveals. The concept “the training environment” as a component of last generation information technology of education is considered. Modern lines in the organization of training environments are allocated.
Keywords: інноваційні технології; телекомунікаційні технології; навчальна діяльність; технології навчання